(untitled) (Archives of Criminology, 1987)
The family, the child’s first environment in which his social traits are formed, is imposed upon him and all it is able and wants to offer him is given to him without his consent, choice, and frequently awareness. The parents or persons who replace them decide for the child and organize his existence in his interest in the early stages of his life, and hand down to him the norm sand values according to their own consciousness and beliefs. All of their activities, aimed at the child and at other persons or things as well as their way of perception of and reaction to outer factors, constitute the fabric from which the child derives patterns for his own behaviour. The parents and the closest environment shape the child’s attitude towards himself and other persons through purposeful action and through situations specially created or rendered accessible to the child. In the early childhood in particular, before the child goes to school, his parents play the leading part in his development. For this reason, their human quality is of importance. Despite the fact that there is a vast literature on the family the specialists and practicians in social sciences keep submitting new problems that want explanation. The prognosis of the child’s future fate depends first of all on his family environment. The child’s socialization, development and mental growth take a normal course if conditions have been provided for his needs to be satisfied. Particularly in the case of a child, the need of love, and attachment predominates among mental needs, with that of favourable contacts with other persons developing somewhat later. A child accepted by his family and cherished with affection –provided he is convinced of that - feels safe and believes that his guardians act for his benefit. The climate at home which is created first and foremost by the parents, is not only important for the child’s development but frequently leaves permanent traces in the mind of an adult –often as patterns of behaviour. Children devoid of favourable conditions of socialization in their families often cause serious educational problems and are commonly defined as difficult. The origins of their maladjustment can first of ,all be found in a faulty socialization which makes them more open to bad influence and more apt to break the obligatory social and legal norms. In studies of juvenile delinquents, the symptoms of disturbances in their families are usually found. Divorce is always a result of certain anomalies within the family and brings about disadvantageous conditions for the child’s socialization. The future way or life of the child is usually difficult to forecast, during proceedings before the court in particular. For this reason, in more difficult or even doubtful cases, the court appoints an expert who is usually a psychologist or an educator. Admittedly, the expert’s observations and findings influence the court’s decision; yet after the decision has become valid and the further course of events does not call for reopening of the proceedings, hardly anybody cares whether the decision concerning the child was really in his interest and whether the situation imposed upon him corresponds with his wishes. At the Faculty of Psychology of the Warsaw University, examinations ordered by the court have for many years been performed in case of children and young persons, including divorce cases of parents, Examination took at least 2-3 visits which rendered possible a comprehensive appraisal of the environment and of the child entangled in his parents conflict. Examination ordered by the court went beyond the child’s future situation, including his past and future as well. This made it possible to roughly estimate the influence of a new family situation on the further course of the child’s mental development and process of socialization. A follow-up was planned beforehand to verify the conclusions of the examination and the court’s decision. It was interesting to learn about the child’s further fate, to compare it with the earlier prognosis, and to examine the child’s attitude towards his previous situation (during his parents divorce) and the influence it exerted on him. The above follow-up was conducted in 1984. A hundred persons from Warsaw who had grown of age after the divorce proceedings were included in the study. Therefore, while at the moment of the examination the youngest examined person was aged 2, and the eldest nearly 18, at the moment of follow-up, the previously examined as children were aged 18 to over 30. The time between these two examinations varied from 5 to over 17 years. Only the youngest subjects were just finishing secondary school or starting higher education or some kind of professional training at the time of the follow-up. The elder ones were students or those starting their professional career, while the eldest ones prepared to set up a family and an independent life. The follow-up provides data to verify the prognosis which may either be confirmed or prove incorrect, particularly if new circumstances emerged (or those unknown before) that vitally influenced the examined person’s fate. The follow-up may be related to the prognosis in the following four ways: the prognosis was positive which is confirmed by the follow-up (P+F+); the prognosis was negative and negative data are also provided by the follow-up (P-F-); the prognosis was positive which is however not fonfirmed by the follow-up (P+F-); the prognosis was negative but the follow-up appears positive (P -F +). The findings of the follow-up were included in all of the above four group’s as follows: P+F+ 82 cases P- F- 4 cases P+F - 6 cases P-F+ 8 cases There were no surprises in the extreme groups: the fates of the child were anticipated to take a favourable course provided the court takes the expert’s conclusions into account (P+F+); or the prognosis was bad irrespectively of the court’s possible decision (P- F-). On the other hand, in the groups where the follow-up failed to confirm the prognosis, either the diagnosis was wrong or new facts occurred after the examination which conclusively influenced the child’s situation. The most numerous was the group of cases in which follow-up confirmed a favourable prognosis. In those cases, the family environment involved was different, as much as the parents mentality and personality traits, cultural standards, living conditions, the child’s emotional ties with his parents and many other features. However, there were certain common features which favourably influenced the child’s fate and they justified good prognosis. Divorcing parents accepted the court’s decision truly in the child’s interest pushing their own wishes and ambitions to the background. They remained loyal to each other and respected the child’s rights. They were able to create a climate which guaranteed the feeling of safety of the child and respect for his affection towards the parents. In these conditions, the effects of divorce were less painful for the child and the child could regain mental balance shaken by his parents conflict. In the cases where follow-up confirmed a negative prognosis, the parents considered divorce proceedings to be their business exclusively. The child was just a supplement to their lives which they did not take into consideration; they provided no support for the child who had to depend on himself only, trying to overcome difficulties for which he was not prepared. The fates of the children in the case of whom prognosis proved not consistent with follow-up are interesting. A change for the better meant that the expertise and the court’s decision mobilized the parents, and the subsequent course of events confirmed the fact that parents are indispensable if they act in genuine good faith, manifesting kindness towards the child and mutual tolerance and trust. In the last group, the follow-up failed to confirm a favourable prognosis. This was due to facts that occurred some time after the first examination and were difficult to anticipate, which negatively influenced the child’s fate (e.g. death of a good guardian). The follow-up made it possible to verify the relevance of methods applied in the examination as well as its general conception, according to which the child referred by the court for examination is an important but not the only element of his parents divorce. In such cases, the expert examines in a different way and context and from a different point of view the same problems in which the court is interested; however, he is able to examine more extensively and penetratingly the conditions that are inaccessible or difficult of access for the court, due to the lack of professional knowledge if not for other reasons. The follow-up confirmed the importance of the family in the child’s education and socialization. A broken home creates conditions that can eventually lead to a minor’s maladjustment: if there are no factors to stop it, a broken home may produce a delinquency originating situation for the child.